Sensory abilities in food localization in four species of African mole-rats with diverse social organization - Vitámvás, Miloš (Jihočeská univerzita, 2013)
Until recently, it was assumed that African mole-rats search for food randomly, as it is in concordance with Aridity food distribution hypothesis. However, recent studies indicate that some subterranean rodent species including mole-rats could be able to use plant chemicals (kairomones) for food localization. In my master thesis I conducted a battery of experiments on four mole-rat species to prove, that these species also posses the ability of kairomone guided foraging independently of their social organization.
Sensory abilities and food localization in four species of African mole-rats with diverse social organization
Keywords: mole-rat; Bathyergidae; subterranean rodent; foraging; kairomone; food localization; mole-rat; Bathyergidae; subterranean rodent; foraging; kairomone; food localization